276 Improving the quality of prostate cancer diagnosis and treatment using shared clinical practice indicators (CPI) and a computerised clinical pathway. (23rd September 2015) - Rébillard, X; Ségui, B; Faix, A; Hamid, S Abdel; Murez, T; Daniel, R; Riolacci, N; Erbault, M; Desplanques, A; Pierre, D; Coloby, P; ,
Abstract : Background and Objectives: In France, prostate cancer is the most common cancer in men (71 000 new cases expected in 2009) and the second cause of mortality from cancer (8600 deaths expected in 2009). About 180 000 biopsies are made each year, enabling diagnosis of the disease when still at a localised stage in 70% of cases. Radical prostatectomy (RP) (about 25 000 per year) is a therapeutic option for localised cancer requiring the management of the risk of incomplete tumour excision as well as of postoperative functional morbidity. In 2009, the French Parliamentary Office for the Assessment of Health Policies underscored inconsistencies in prostate cancer management that impact on functional morbidity and mortality. Our objective was to develop clinical practice indicators (CPIs) for inclusion in a computerised clinical pathway to be able to propose improvements in care, whether with regard to diagnostic or therapeutic decisions. Programme: The CPIs were based on clinical practice guidelines selected by a panel of urologists and validated by the French Association of Urologists (AFU). The innovative computer system Normind-diagnosis was used to calculate CPI values from patient records. The feasibility and quality of CPI data collection by Normind-diagnosis was validated in an analysis of records from five urology departments and national or regional databases (multidisciplinary review of medical records, the pathology database of CRISAP-LR, the national ABLATHERM registry, and the FRANCIM 2001 cohort). The criteria for assessing the quality and safety of diagnostic and therapeutic care in RP patients were: Quality of the histology report (compliance with the recommendations of the AFU Cancer Committee (CCAFU) and the French Society of Pathology), Correct selection of patients eligible for surgery (D' Amico risk classification, comorbidities) and safety of surgery (transfusion rate), Efficacy in oncological terms (negative surgical margins, undetectable PSA at 3 months), and Detection of postoperative functional morbidity and assessment of quality of life (continence at 1 year, erectile dysfunction at 2 years). Results: A total of 545 patients with prostate cancer diagnosed in 2007–2008 benefited from CPI monitoring. The CPIs could be calculated from 89% of patient records: In 2008, 100% of biopsy histology reports complied with CCAFU criteria versus 67% in 2007. The D'Amico prognostic group was determined in 98% of patients. For 185 patients who underwent RP, the decision was completely in line with all good practice criteria in 89% of cases; 1% of patients had transfusions. Surgical margins were negative in 84% of patients; 97% had undetectable PSA at 3 months. 91% of patients were totally continent at 1 year. Data for erectile dysfunction are not available. Discussion and Conclusion: This computerised clinical pathway using CPIs is currently being implemented by eight urology teams in three regions in France within the framework of a quality research programme (PREQHOS). Patients undergoing RP for localised cancer are entered prospectively. This practice registry will enable teams to exchange experiences and observe their trends in practice. The first results are expected in 2010.""" Contexte: Le cancer de la prostate est un problème de santé publique en France par sa fréquence (1er cancer chez l'homme, 71 000 nouveaux cas attendus en 2009) et sa mortalité (2ème cause de mortalité avec 8600 décès attendus pour 2009). Environ 180 000 biopsies diagnostiques sont effectuées par an permettant le diagnostic des tumeurs à un stade localisé dans 70% des cas. La prostatectomie (environ 25 000 par an) est l'une des options thérapeutiques pour les cancers localisés. Les contraintes d'une exérèse carcinologiquement efficace et le risque de morbidité fonctionnelle post opératoire imposent une très haute qualité d'indication et de prise en charge tout au long de la trajectoire de soins du patient. En 2009, l'Office Parlementaire d'Evaluation des Politiques de Santé souligne l'hétérogénéité des prises en charge avec une traduction sur la morbidité fonctionnelle induite et la mortalité. Objectif—programme: Un chemin clinique informatisé incluant le suivi d'indicateurs de pratique clinique (IPC) permet de tracer les arguments fondant les décisions diagnostiques ou thérapeutiques pour une file active de patients. Il permet d'objectiver la qualité de la prise en charge et le cas échéant de proposer des actions d'amélioration du parcours de soins du patient. Les IPC sont issus des recommandations de bonnes pratiques, sélectionnés par un panel de d'urologues et validés par la société savante d'urologie (AFU). Le système informatique innovant Normind-diagnosis calcule les IPC à partir des informations structurées du dossier médical des patients. La faisabilité et la qualité du recueil des IPC par le système informatique Normind-diagnosis ont été validées par l'analyse des dossiers médicaux de 5 services d'urologie et de bases nationales ou régionales (réunions de concertation pluridisciplinaires (RCP), bases de pathologie du CRISAP-LR, registre national Ablatherm et cohorte FRANCIM 2001). La démarche permet d'objectiver la qualité et la sécurité de la prise en charge diagnostique et thérapeutique des cancers localisés sur les critères suivants: la qualité du compte rendu de l'étude histologique (conformité du compte rendu aux recommandations du CCAFU et de la Société Française de Pathologie), la juste sélection des patients éligibles à la chirurgie (groupe de d'Amico, co-morbidités) et la sécurité de la prise en charge chirurgicale (taux de transfusion), l'efficacité carcinologique (marges d'exérèse négatives et PSA indétectable à 3 mois), le repérage des séquelles fonctionnelles post opératoires et la qualité de vie des patients (taux de continence à un an, dysfonction érectile à 2 ans). Résultats: 545 patients atteints de cancer de la prostate diagnostiqués en 2007–2008 ont bénéficié d'un suivi d'indicateurs de pratique clinique. Les données du dossier médical ont permis le calcul des IPC pour 89% des patients avec les résultats suivants: En 2008, 100% des comptes rendus d'histologie relatifs aux biopsies prostatiques répondent aux critères de qualité retenus par CCAFU contre 67% en 2007. Le groupe pronostique de d'Amico a été déterminé pour 98% des patients. Pour les 185 patients ayant bénéficié d'une prostatectomie, la décision est complètement tracée et conforme à tous les critères des recommandations de bonne pratique dans 89% des cas. 1% ont été transfusés. Les marges d'exérèse étaient négatives pour 84% d'entre eux et 97% ont un PSA indétectable à 3 mois. 91% des patients sont totalement continents à 1 an. Les données de dysfonction érectile ne sont actuellement pas disponibles. Discussion et perspectives: Le chemin clinique informatisé avec IPC est actuellement mis en place auprès de 8 équipes d'urologues de 3 régions françaises dans le cadre d'un programme de recherche sur la qualité (PREQHOS) avec inclusion en prospectif des patients traités par prostatectomie pour un cancer localisé. Ce registre de pratique permettra aux équipes d'échanger sur leurs pratiques, et de disposer pour chacune d'entre elles d'un suivi dans le temps qui objectivera l'évolution de leurs pratiques. Les premiers résultats sont attendus pour 2010.